Variation in temperature and light but not salinity invokes antioxidant enzyme activities in germinating seeds of Salsola drummondii. (2nd September 2016) - Rasheed, A.; Hameed, A.; Khan, M. A.; Gul, B.
Abstract : Seeds with efficient antioxidant defence system show higher germination under stress conditions; however, such information is limited for the halophyte seeds. We therefore studied lipid peroxidation and antioxidant responses of a leaf-succulent halophyte Salsola drummondii during seed germination under different salinity levels (0, 200 and 800 mM NaCl), temperature (10/20, 20/30 and 25/35°C) and light regimes. Seeds absorbed water and germinated in less than 1 h in non-saline control while increases in salinity decreased the rate of water uptake as well as seed germination. Non-optimal temperatures (10/20 and 25/35°C) and complete dark condition reduced seed germination in comparison to those seeds germinated under optimal temperature (20/30°C) and 12-h photoperiod, respectively. Generally, higher lipid peroxidation and antioxidant enzyme activities were observed in seeds at non-optimal temperature and in those seeds germinated in dark. Decrease in reduced ascorbic acid content was found in highest salinity and temperature treatments, while reduced glutathione content did not change significantly with changes in salinity, temperature and light regimes. These results indicate variation in temperature and light but not salinity enhances antioxidant enzyme activities in germinating seeds of Salsola drummondii .